Environmentally Friendly Particle Board - Saipol Bahadi, Muhammad Izzul Khairi; Muhammad Nazmi Amirul Akmam Norhisham,; Muhammad Faris Izzudin Zulkifli izzudin,; Khairul Zaman Abdul Malek, (Multidisciplinary Applied Research and Innovation, 2023)
This article explores the use of the sugarcane waste as a replacement for the wood dust in the making of fiberboard since the dust can affect our environment and health. The waste of sugarcane dumped from the machine that make the juice might cause environmental pollution and also make the surroundings feel uncomfortable. The main objective of this project is to produce a fiberboard by mixing the sugarcane waste with different amount of adhesive material by applying technology of compressing. Density test and water absorption test conducted on the samples. It is interesting to find out the sugarcane waste able to replace the wood dust to make particle board.